Numerical study on the flexural performance of precast segmental concrete beams with unbonded internal steel tendons - Le, T.D.; Pham, Thong; Hao, Hong (ELSEVIER SCI LTD, 2020)
This study presents a numerical investigation of the flexural performance of precast segmental concrete beams (PSBs) with unbonded internal steel tendons. Numerical models developed in this study using Abaqus software capture well the responses of the PSBs reported in previous studies. This is the first time a three-dimensional numerical model is built and successfully validated against experimental results of PSBs in literature. Based on the verified numerical model, intensive simulations of performances of segmental beams with different parameters and various conditions, i.e. tension-controlled, compression-controlled and balanced sections, are carried out. Based on the numerical results, the flexural behaviour of PSBs under four-point loading is extensively discussed regarding the failure modes, joint opening, stress increment in the tendon and the stress transfer mechanism. A parametric study is also conducted and the results show that the effective prestress, prestressing steel reinforcement ratio, and span length-to-tendon depth ratio strongly affect the load-carrying capacity, ductility, tendon stress increment, joint opening and failure modes of PSBs with unbonded tendons, while the loading type, concrete strength and the number of joints show insignificant effects on the flexural performance of the structure.